K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 2 2020

a)Gọi I là trung điểm BC \(\Rightarrow\hept{\begin{cases}OI\perp BC\\BI=CI=\frac{R\sqrt{3}}{2}\end{cases}}\)Ta có\(\sin\widehat{BOI}=\frac{BI}{OB}=\frac{\frac{\sqrt{3}}{2}R}{R}=\frac{\sqrt{3}}{2}\Rightarrow\widehat{BOI}=60^o\) \(\Rightarrow\widehat{BOC}=120^o\)

b) Ta có \(\widebat{BC}=\widehat{BOC}=120^o\) Mà\(\Rightarrow\widehat{BAC}=\frac{\widebat{BC}}{2}\)\(\Rightarrow\widehat{BAC}=60^o\)

Bài 3:

a) Ta có: \(4+2\sqrt{3}\)

\(=3+2\cdot\sqrt{3}\cdot1+1\)

\(=\left(\sqrt{3}+1\right)^2\)

b) Ta có: \(7+4\sqrt{3}\)

\(=4+2\cdot2\cdot\sqrt{3}+3\)

\(=\left(2+\sqrt{3}\right)^2\)

c) Ta có: \(9+4\sqrt{5}\)

\(=5+2\cdot\sqrt{5}\cdot2+4\)

\(=\left(\sqrt{5}+2\right)^2\)

d) Ta có: \(31+10\sqrt{6}\)

\(=25+2\cdot5\cdot\sqrt{6}+6\)

\(=\left(5+\sqrt{6}\right)^2\)

e) Ta có: \(13+4\sqrt{3}\)

\(=12+2\cdot2\sqrt{3}\cdot1+1\)

\(=\left(2\sqrt{3}+1\right)^2\)

g) Ta có: \(21+12\sqrt{3}\)

\(=12+2\cdot2\sqrt{3}\cdot3+9\)

\(=\left(2\sqrt{3}+3\right)^2\)

h) Ta có: \(29+12\sqrt{5}\)

\(=20+2\cdot2\sqrt{5}\cdot3+3\)

\(=\left(2\sqrt{5}+3\right)^2\)

i) Ta có: \(49+8\sqrt{3}\)

\(=48+2\cdot4\sqrt{3}\cdot1\)

\(=\left(4\sqrt{3}+1\right)^2\)

k) Sửa đề: \(14-6\sqrt{5}\)

Ta có: \(14-6\sqrt{5}\)

\(=9-2\cdot3\cdot\sqrt{5}+5\)

\(=\left(3-\sqrt{5}\right)^2\)

l) Ta có: \(23-8\sqrt{7}\)

\(=16-2\cdot4\cdot\sqrt{7}+7\)

\(=\left(4-\sqrt{7}\right)^2\)

m) Ta có: \(15-4\sqrt{11}\)

\(=11-2\cdot\sqrt{11}\cdot2+4\)

\(=\left(\sqrt{11}-2\right)^2\)

n) Sửa đề: \(28-10\sqrt{3}\)

Ta có: \(28-10\sqrt{3}\)

\(=25-2\cdot5\cdot\sqrt{3}+3\)

\(=\left(5-\sqrt{3}\right)^2\)

o) Ta có: \(17-12\sqrt{2}\)

\(=9-2\cdot3\cdot2\sqrt{2}+8\)

\(=\left(3-2\sqrt{2}\right)^2\)

p) Ta có: \(43-30\sqrt{2}\)

\(=25-2\cdot5\cdot3\sqrt{2}+18\)

\(=\left(5-3\sqrt{2}\right)^2\)

q) Ta có: \(51-10\sqrt{2}\)

\(=50-2\cdot5\sqrt{2}\cdot1\)

\(=\left(5\sqrt{2}-1\right)^2\)

r) Ta có: \(49-12\sqrt{5}\)

\(=45-2\cdot3\sqrt{5}\cdot2+4\)

\(=\left(3\sqrt{5}-2\right)^2\)

7 tháng 6 2019

\(\sqrt{11+6\sqrt{2}}-\sqrt{2}\text{=}\sqrt{9+6\sqrt{2}+4}-\sqrt{2}\)

=\(\sqrt{\left(3+\sqrt{2}\right)^2}-\sqrt{2}\text{=}3+\sqrt{2}-\sqrt{2}=3\)

7 tháng 6 2019

a/ \(\sqrt{11+6\sqrt{2}}-\sqrt{2}=\sqrt{9+6\sqrt{2}+2}-\sqrt{2}=\sqrt{\left(3+\sqrt{2}\right)^2}-\sqrt{2}=3+\sqrt{2}-\sqrt{2}=3\)

b/ \(\sqrt{28-10\sqrt{3}}+5=\sqrt{25-10\sqrt{3}+3}+5\)

\(=\sqrt{\left(5-\sqrt{3}\right)^2}+5=5-\sqrt{3}+5=25-\sqrt{3}\)

c/ \(\sqrt{4+2\sqrt{3}}-\sqrt{4-2\sqrt{3}}=\sqrt{3+2\sqrt{3}+1}-\sqrt{3-2\sqrt{3}+1}\)

\(=\sqrt{\left(\sqrt{3}+1\right)^2}-\sqrt{\left(\sqrt{3}-1\right)^2}\)

\(=\sqrt{3}+1-\sqrt{3}+1=2\)

d/ \(3\sqrt{5}-\sqrt{6-2\sqrt{5}}=3\sqrt{5}-\sqrt{5-2\sqrt{5}+1}\)\

\(=3\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}=3\sqrt{5}-\sqrt{5}+1=2\sqrt{5}+1\)

a) Ta có: \(\sqrt{11-2\sqrt{10}}\)

\(=\sqrt{10-2\cdot\sqrt{10}\cdot1+1}\)

\(=\sqrt{\left(\sqrt{10}-1\right)^2}\)

\(=\left|\sqrt{10}-1\right|=\sqrt{10}-1\)

b) Ta có: \(\sqrt{9-2\sqrt{14}}\)

\(=\sqrt{7-2\cdot\sqrt{7}\cdot\sqrt{2}+2}\)

\(=\sqrt{\left(\sqrt{7}-\sqrt{2}\right)^2}\)

\(=\left|\sqrt{7}-\sqrt{2}\right|\)

\(=\sqrt{7}-\sqrt{2}\)

c) Ta có: \(\sqrt{4+2\sqrt{3}}+\sqrt{4-2\sqrt{3}}\)

\(=\sqrt{3+2\cdot\sqrt{3}\cdot1+1}+\sqrt{3-2\cdot\sqrt{3}\cdot1+1}\)

\(=\sqrt{\left(\sqrt{3}+1\right)^2}+\sqrt{\left(\sqrt{3}-1\right)^2}\)

\(=\left|\sqrt{3}+1\right|+\left|\sqrt{3}-1\right|\)

\(=\sqrt{3}+1+\sqrt{3}-1\)

\(=2\sqrt{3}\)

d) Ta có: \(\sqrt{9-4\sqrt{5}}-\sqrt{9+4\sqrt{5}}\)

\(=\sqrt{5-2\cdot\sqrt{5}\cdot2+4}-\sqrt{5+2\cdot\sqrt{5}\cdot2+4}\)

\(=\sqrt{\left(\sqrt{5}-2\right)^2}-\sqrt{\left(\sqrt{5}+2\right)^2}\)

\(=\left|\sqrt{5}-2\right|-\left|\sqrt{5}+2\right|\)

\(=\sqrt{5}-2-\left(\sqrt{5}+2\right)\)

\(=\sqrt{5}-2-\sqrt{5}-2\)

\(=-4\)

e) Ta có: \(\sqrt{4-\sqrt{7}}-\sqrt{4+\sqrt{7}}\)

\(=\frac{\sqrt{2}\cdot\left(\sqrt{4-\sqrt{7}}-\sqrt{4+\sqrt{7}}\right)}{\sqrt{2}}\)

\(=\frac{\sqrt{2}\cdot\left(\sqrt{4-\sqrt{7}}\right)-\sqrt{2}\cdot\left(\sqrt{4+\sqrt{7}}\right)}{\sqrt{2}}\)

\(=\frac{\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}}{\sqrt{2}}\)

\(=\frac{\sqrt{7-2\cdot\sqrt{7}\cdot1+1}-\sqrt{7+2\cdot\sqrt{7}\cdot1+1}}{\sqrt{2}}\)

\(=\frac{\sqrt{\left(\sqrt{7}-1\right)^2}-\sqrt{\left(\sqrt{7}+1\right)^2}}{\sqrt{2}}\)

\(=\frac{\left|\sqrt{7}-1\right|-\left|\sqrt{7}+1\right|}{\sqrt{2}}\)

\(=\frac{\sqrt{7}-1-\left(\sqrt{7}+1\right)}{\sqrt{2}}\)

\(=\frac{\sqrt{7}-1-\sqrt{7}-1}{\sqrt{2}}\)

\(=\frac{-2}{\sqrt{2}}=-\sqrt{2}\)

g) Ta có: \(\sqrt{3}+\sqrt{11+6\sqrt{2}}+\sqrt{5+2\sqrt{6}}\)

\(=\sqrt{3}+\sqrt{9+2\cdot3\cdot\sqrt{2}+2}+\sqrt{2+2\cdot\sqrt{2}\cdot\sqrt{3}+3}\)

\(=\sqrt{3}+\sqrt{\left(3+\sqrt{2}\right)^2}+\sqrt{\left(\sqrt{2}+\sqrt{3}\right)^2}\)

\(=\sqrt{3}+\left|3+\sqrt{2}\right|+\left|\sqrt{2}+\sqrt{3}\right|\)

\(=\sqrt{3}+3+\sqrt{2}+\sqrt{2}+\sqrt{3}\)

\(=3+2\sqrt{3}+2\sqrt{2}\)

h) Ta có: \(\sqrt{5\sqrt{3}+5\sqrt{48-10\sqrt{7+4\sqrt{3}}}}\)

\(=\sqrt{5\sqrt{3}+5\sqrt{48-10\cdot\sqrt{3+2\cdot\sqrt{3}\cdot2+4}}}\)

\(=\sqrt{5\sqrt{3}+5\sqrt{48-10\cdot\sqrt{\left(\sqrt{3}+2\right)^2}}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\sqrt{48-10\cdot\left(\sqrt{3}+2\right)}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\sqrt{48-10\sqrt{3}-20}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\sqrt{28-10\sqrt{3}}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\sqrt{25-2\cdot5\cdot\sqrt{3}+3}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\sqrt{\left(5-\sqrt{3}\right)^2}}\)

\(=\sqrt{5\sqrt{3}+5\cdot\left(5-\sqrt{3}\right)}\)

\(=\sqrt{5\sqrt{3}+25-5\sqrt{3}}\)

\(=\sqrt{25}=5\)

k) Ta có: \(\sqrt{94-42\sqrt{5}}-\sqrt{94+42\sqrt{5}}\)

\(=\sqrt{49-2\cdot7\cdot\sqrt{45}+45}-\sqrt{49+2\cdot7\cdot\sqrt{45}+45}\)

\(=\sqrt{\left(7-\sqrt{45}\right)^2}-\sqrt{\left(7+\sqrt{45}\right)^2}\)

\(=\left|7-\sqrt{45}\right|-\left|7+\sqrt{45}\right|\)

\(=7-\sqrt{45}-\left(7+\sqrt{45}\right)\)

\(=7-\sqrt{45}-7-\sqrt{45}\)

\(=-2\sqrt{45}=-6\sqrt{5}\)

i) Đặt \(A=\sqrt{4+\sqrt{10+2\sqrt{5}}}+\sqrt{4-\sqrt{10+2\sqrt{5}}}\)

\(\Leftrightarrow A^2=\left(\sqrt{4+\sqrt{10+2\sqrt{5}}}+\sqrt{4-\sqrt{10+2\sqrt{5}}}\right)^2\)

\(=4+\sqrt{10+2\sqrt{5}}+4-\sqrt{10+2\sqrt{5}}+2\cdot\sqrt{\left(4+\sqrt{10+2\sqrt{5}}\right)\cdot\left(4-\sqrt{10+2\sqrt{5}}\right)}\)

\(=8+2\cdot\sqrt{16-\left(10+2\sqrt{5}\right)}\)

\(=8+2\cdot\sqrt{6-2\sqrt{5}}\)

\(=8+2\cdot\sqrt{\left(\sqrt{5}-1\right)^2}\)

\(=8+2\cdot\left(\sqrt{5}-1\right)\)

\(=8+2\sqrt{5}-2\)

\(=6+2\sqrt{5}\)

\(=\left(\sqrt{5}+1\right)^2\)

\(\Leftrightarrow A=\sqrt{5}+1\)

31 tháng 7 2017

https://hoc24.vn/hoi-dap/question/407636.html

\(M=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-10\sqrt{7+4\sqrt{3}}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-10\sqrt{\left(2+\sqrt{3}\right)^2}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-20-10\sqrt{3}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{\left(5-\sqrt{3}\right)^2}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+25-5\sqrt{3}}}\)

\(=\sqrt{4+5}\)

= 9

~ ~ ~ ~ ~

\(M=\sqrt{6+2\sqrt{2}\sqrt{3-\sqrt{\sqrt{2}+\sqrt{12}+\sqrt{18-8\sqrt{2}}}}}\)

\(=\sqrt{6+2\sqrt{2}\sqrt{3-\sqrt{\sqrt{2}+\sqrt{12}+\sqrt{\left(4-\sqrt{2}\right)^2}}}}\)

\(=\sqrt{6+2\sqrt{2}\sqrt{3-\sqrt{\sqrt{2}+2\sqrt{3}+4-\sqrt{2}}}}\)

\(=\sqrt{6+2\sqrt{2}\sqrt{3-\sqrt{\left(\sqrt{3}+1\right)^2}}}\)

\(=\sqrt{6+2\sqrt{2}\sqrt{3-\sqrt{3}-1}}\)

\(=\sqrt{6+2\sqrt{4-2\sqrt{3}}}\)

\(=\sqrt{6+2\sqrt{\left(\sqrt{3}-1\right)^2}}\)

\(=\sqrt{6+2\sqrt{3}-2}\)

\(=\sqrt{\left(\sqrt{3}+1\right)^2}\)

\(=\sqrt{3}+1\)

31 tháng 7 2017

\(M=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{29-12\sqrt{5}}}}\)

\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{\left(2\sqrt{5}-3\right)^2}}}\)

\(=\sqrt{\sqrt{5}-\sqrt{3-2\sqrt{5}+3}}\)

\(=\sqrt{\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}}\)

\(=\sqrt{\sqrt{5}-\sqrt{5}+1}\)

= 1

Chọn D

15 tháng 7 2018

\(1a.\left(\sqrt{72}-3\sqrt{5}+2\sqrt{8}\right).\sqrt{2}+\sqrt{90}=\sqrt{144}-3\sqrt{10}+2.\sqrt{16}+3\sqrt{10}=12+8=20\) \(b.\left(\sqrt{\dfrac{1}{5}}-10\sqrt{\dfrac{27}{5}}+2\sqrt{5}\right):\sqrt{5}+6\sqrt{3}=\left(\sqrt{\dfrac{1}{5}}-30\sqrt{\dfrac{3}{5}}+2\sqrt{5}\right).\dfrac{1}{\sqrt{5}}+6\sqrt{3}=\dfrac{1}{5}-6\sqrt{3}+2+6\sqrt{3}=\dfrac{11}{5}\) \(2.\sqrt{\left(3-\sqrt{10}\right)^2}=\sqrt{10}-3\)

\(b.\sqrt{7+4\sqrt{3}}+\sqrt{7-4\sqrt{3}}=\sqrt{4+2.2\sqrt{3}+3}+\sqrt{4-2.2.\sqrt{3}+3}=2+\sqrt{3}+2-\sqrt{3}=4\) \(c.\dfrac{2+\sqrt{2}}{1+\sqrt{2}}=\dfrac{\sqrt{2}\left(\sqrt{2}+1\right)}{1+\sqrt{2}}=\sqrt{2}\)

Bài 2:

a: \(=\sqrt{5}-2\)

b: \(=2\sqrt{3}+4\sqrt{3}-5\sqrt{3}-9\sqrt{3}=-8\sqrt{3}\)

c: \(=\sqrt{4+2\sqrt{2}}\cdot\sqrt{4-2\sqrt{2}}=\sqrt{16-8}=2\sqrt{2}\)

d: \(=\sqrt{2}+1-2+\sqrt{2}=2\sqrt{2}-1\)

e: \(=\dfrac{8-2\sqrt{15}+8+2\sqrt{15}}{2}-\dfrac{6+2\sqrt{5}}{4}\)

\(=\dfrac{16-3-\sqrt{5}}{2}=\dfrac{13-\sqrt{5}}{2}\)

f: \(=\sqrt{5\sqrt{3+5\sqrt{48-10\left(2+\sqrt{3}\right)}}}\)

\(=\sqrt{5\sqrt{3+5\sqrt{28-10\sqrt{3}}}}\)

\(=\sqrt{5\sqrt{3+5\left(5-\sqrt{3}\right)}}\)

\(=\sqrt{5\sqrt{3+25-5\sqrt{3}}}\)

\(=\sqrt{5\sqrt{28-5\sqrt{3}}}\)